2021
DOI: 10.1001/jamanetworkopen.2021.3687
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth and the Development of Visual Attention During the First 2 Years of Life

Abstract: IMPORTANCE Preterm birth is associated with an increased risk for long-lasting attention deficits.Early-life markers of attention abnormalities have not been established to date but could provide insights into the pathogenesis of attention abnormalities and could help identify susceptible individuals.OBJECTIVE To examine whether preterm birth is associated with visual attention impairments in early life, and if so, in which attention functions and at which developmental period during the first 2 years of life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 133 publications
(334 reference statements)
2
30
0
1
Order By: Relevance
“…Our results demonstrated that abnormal maternal FT4 concentrations might attribute to a higher risk of PTD. Maternal thyroid hormone concentrations in the first trimester are pivotal for fetal growth (24,27) and neurodevelopment (5,7,28) when the fetus depends solely on maternal thyroid hormones via transplacental transition (29). However, epidemiological research has shown inconsistent evidence concerning mild alterations of maternal thyroid function during pregnancy and PTD (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrated that abnormal maternal FT4 concentrations might attribute to a higher risk of PTD. Maternal thyroid hormone concentrations in the first trimester are pivotal for fetal growth (24,27) and neurodevelopment (5,7,28) when the fetus depends solely on maternal thyroid hormones via transplacental transition (29). However, epidemiological research has shown inconsistent evidence concerning mild alterations of maternal thyroid function during pregnancy and PTD (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…PTD annually affects ~15 million newborns globally with 1.2 million (7.8%) in China (4). Furthermore, preterm birth children are at increased risk of serious illness (e.g., lung immaturity, infection) and are susceptive to neurodevelopmental, cognitive, cardiovascular, and metabolic disorders in adulthood (5)(6)(7)(8)(9). Although several risk factors for PTD have been reported (e.g., history of PTD, advanced maternal age, low socioeconomic status, exposure to smoking or narcotics) (1,10), the mechanisms that lead to PTD is still not understood.…”
Section: Introductionmentioning
confidence: 99%
“…The anterior attention network, comprised of the executive attention network ( Davis et al, 2002 ; Krieber-Tomantschger et al, 2022 ), buds in early infancy ( Colombo, 2001 ) when novelty seeking is already present but has a protracted developmental trajectory expressed in growing activation and connectivity as a function of age ( Burstein et al, 2021 ). The anterior attention network presents significant development between 3 and 7 years, reaching full maturation only in adulthood ( Rueda et al, 2005 ; Rothbart et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies of VP infants suggest that problems in learning and behaviour stem from difficulties in the way they regulate and control the acquisition of information from an early age [ 14 18 ]. A crucial role is played by VP infants’ anomalies in attention control, the ability to voluntarily determine what to pay attention to, and what to ignore.…”
Section: Introductionmentioning
confidence: 99%
“…A crucial role is played by VP infants’ anomalies in attention control, the ability to voluntarily determine what to pay attention to, and what to ignore. This ability starts to emerge around the first year of life in typically-developing infants [ 19 , 20 ], and marks a transition from infants’ attention being highly reactive and directed externally by the environment, to their attention being directed voluntarily in accordance with the infants’ goals [ 14 ]. Attention control is considered a key precursor of general top-down abilities to control cognitive processes in the service of goals such as Executive Functions (EFs) [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%